United Security Council Reform: A Philosophical Perspective on the Abolition of the Veto - Rizal, Muhammad (Riviera Publishing, 2026)
The reform of the United Nations Security Council (UNSC) has become an important topic in international relations studies, particularly regarding the veto power held by the five permanent members. This veto power creates structural injustice by reinforcing the dominance of major powers and neglecting the principles of equality and collective responsibility in maintaining global peace. A philosophical perspective reveals the tension between the moral legitimacy of global democracy and the authoritarian authority that can block vital humanitarian decisions, such as interventions to stop genocide. This study aims to analyze the impact of veto power on the UNSC's ability to address humanitarian crises and human rights violations, as well as to evaluate the application of cosmopolitan justice principles in the decisions made by the five permanent members of the UNSC. The research methodology is normative-doctrinal with a literature review, incorporating Rawls's theory of justice and the concept of cosmopolitan justice. The findings indicate that the veto obstructs swift responses to humanitarian crises and exacerbates inequality in global governance. In conclusion, UNSC reform is necessary, specifically through limiting or abolishing the veto power, to enhance justice, legitimacy, and collective effectiveness in maintaining international peace.